Asymptotic analysis of thin elastic junction between two elastic bodies. Issue 3 (11th February 2023) - Khludnev, A. M.
Abstract : In this paper, an equilibrium problem for two elastic bodies connected by a thin junction (bridge) is analyzed. An existence of solutions is proved. Passages to limits are justified with respect to the rigidity parameter of the junction. In particular, the rigidity parameter tends to infinity and to zero. Limit models are investigated.